1993
DOI: 10.1016/0378-1097(93)90150-z
|View full text |Cite
|
Sign up to set email alerts
|

Vascular permeability enhancing activity of Porphyromonas gingivalis protease in guinea pigs

Abstract: Porphyromonas gingivalis protease, which had been isolated from a culture supernatant, caused vascular permeability enhancement in a dose-dependent manner when injected into guinea pig skin. The permeability-enhancing reaction caused by the protease was not affected by treatment with antihistamine, but was greatly augmented by simultaneous injection of a kinin potentiator, carboxypeptidase N inhibitor. However, the reaction was inhibited by soybean trypsin inhibitor or alpha 2-antiplasmin, although both of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…Moreover, a mixture of proteinase inhibitors, some of which have been shown to inhibit several steps in the kallikrein/kinin metabolic pathway but not gingipain RgpA activity (1, 12, 14-17, 20, 22), abrogated gingipain RgpA-induced responses. These data support and extend previous studies in the literature that showed that exogenous gingipains activate the kallikrein/kinin metabolic pathway in guinea pig skin and elicit plasma exudation (10,(14)(15)(16).…”
Section: ϫ6supporting
confidence: 91%
See 2 more Smart Citations
“…Moreover, a mixture of proteinase inhibitors, some of which have been shown to inhibit several steps in the kallikrein/kinin metabolic pathway but not gingipain RgpA activity (1, 12, 14-17, 20, 22), abrogated gingipain RgpA-induced responses. These data support and extend previous studies in the literature that showed that exogenous gingipains activate the kallikrein/kinin metabolic pathway in guinea pig skin and elicit plasma exudation (10,(14)(15)(16).…”
Section: ϫ6supporting
confidence: 91%
“…Leupeptin and a mixture of proteinase inhibitors also attenuated GRgpAinduced responses. These data indicate that GRgpA elicits plasma exudation from in situ oral mucosa in a catalytic site-dependent fashion by elaborating bradykinin.A large body of experimental evidence suggests that Porphyromonas gingivalis, an oral anaerobic bacterium, plays a role in the pathogenesis of adult periodontitis (2,9,(13)(14)(15)(16)32). A cardinal manifestation of this condition is plasma exudation from postcapillary venules (11,32).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…One may, however, assume that hemorrhage was caused by the effect of gingipains on the respiratory epithelium, the endothelium lining capillary blood vessels, and components of the coagulation cascade. Degradation of tight-junction proteins by gingipains [74], together with enhanced vascular permeability [75], interference with blood clotting due to degradation of fibrinogen by Kgp [76], and protein C consumption by Rgps [77], most likely facilitate blood flow into lung tissues [78]. Also, the increased influx of neutrophils into the lung tissue of animals infected with W83 may exacerbate the local inflammatory response, thereby increasing tissue damage and, subsequently, bleeding and necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…2). The ability of P. gingivalis proteinases to activate the kallikrein/kinin pathway was first described by Hinode et al 20 and Kaminishi et al 21 and later was studied in detail by Imamura et al 22,23 It was found that gingipains R are very potent vascular permeability enhancement (VPE) factors, inducing this activity through plasma prekallikrein activation and subsequent BK release. In this activity no significant difference was seen between HRgpA and RgpB.…”
Section: Activation Of the Kallikrein/kinin Systemmentioning
confidence: 97%